Oral Trypanosoma cruzi Acute Infection in Mice Targets Primary Lymphoid Organs and Triggers Extramedullary Hematopoiesis - Marins-Dos-Santos, Alessandro; Ayres-Silva, Jackline de Paula; Antunes, Dina; Moreira, Carlos José de Carvalho; Pelajo-Machado, Marcelo; Alfaro, David; Zapata, Agustín G.; Bonomo, Adriana Cesar; Savino, Wilson; de Meis, Juliana; Farias-de-Oliveira, Désio Aurélio (Frontiers in Cellular and Infection Microbiology, 2022)
During the acute phase of Chagas disease, Trypanosoma cruzi circulation through the bloodstream leads to high tissue parasitism in the host. In primary lymphoid organs, progenitor cell reduction paralleled transient immunosuppression. Herein we showed that acute oral infection in mice promotes diffuse parasitism in bone marrow cells at 14 and 21 days post-infection (dpi), with perivascular regions, intravascular regions, and regions near the bone being target sites of parasite replication. Phenotypic analysis of hematopoietic differentiation in the bone marrow of infected mice showed that the cell number in the tissue is decreased (lineage-negative and lineage-positive cells). Interestingly, analysis of hematopoietic branching points showed that hematopoietic stem and progenitor cells (HSPCs) were significantly increased at 14 dpi. In addition, the pool of progenitors with stem plasticity (HSC-MPP3), as well as multipotent progenitors (MPPs) such as MPP4, also showed this pattern of increase. In contrast, subsequent progenitors that arise from MPPs, such as common lymphoid progenitors (CLPs), lymphoid-primed MPPs (LMPPs), and myeloid progenitors, were not enhanced; conversely, all presented numeric decline. Annexin V staining revealed that cell death increase in the initial hematopoietic branching point probably is not linked to CLPs and that myeloid progenitors decreased at 14 and 21 dpi. In parallel, our investigation provided clues that myeloid progenitor decrease could be associated with an atypical expression of Sca-1 in this population leading to a remarkable increase on LSK-like cells at 14 dpi within the HSPC compartment. Finally, these results led us to investigate HSPC presence in the spleen as a phenomenon triggered during emergency hematopoiesis due to mobilization or expansion of these cells in extramedullary sites. Splenocyte analysis showed a progressive increase in HSPCs between 14 and 21 dpi. Altogether, our study shows that the bone marrow is a target tissue in T. cruzi orally infected mice, leading to a hematopoietic disturbance with LSK-like cell bias accounting on HSPCs possibly affecting myeloid progenitor numbers. The LMPP and CLP reduction converges with defective thymocyte development. Lastly, it is tempting to speculate that the extramedullary hematopoiesis seen in the spleen is a mechanism involved in the hematological maintenance reported during the acute phase of oral T. cruzi infection.